2014
DOI: 10.5811/westjem.2014.7.21304
|View full text |Cite
|
Sign up to set email alerts
|

Shock Index and Prediction of Traumatic Hemorrhagic Shock 28-Day Mortality: Data from the DCLHb Resuscitation Clinical Trials

Abstract: IntroductionTo assess the ability of the shock index (SI) to predict 28-day mortality in traumatic hemorrhagic shock patients treated in the diaspirin cross-linked hemoglobin (DCLHb) resuscitation clinical trials.MethodsWe used data from two parallel DCLHb traumatic hemorrhagic shock efficacy trials, one in U.S. emergency departments, and one in the European Union prehospital setting to assess the relationship between SI values and 28-day mortality.ResultsIn the 219 patients, the mean age was 37 years, 64% sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
5

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 35 publications
1
36
0
5
Order By: Relevance
“…Sloan et al reported that trauma patients with an SI ≥1.0, 1.4 and 1.8 at any time point were 2.3, 2.7 and 3.1 times, respectively, more likely to die within 28 days than were patients with SI values below these cut-offs (p<0.001). In the same study, and after 120 min of resuscitation, patients with an SI ≥1.0 were 3.9 times more likely to die within 28 days (40% vs 15%, p<0.001) 24. A recent retrospective study of 20 000 adult patients from the trauma registry demonstrated that an SI of ≥1.4 was associated with worst injury severity score, largest fluid requirements, greatest transfusion requirements and highest proportion of patients transfused.…”
Section: Discussionmentioning
confidence: 84%
“…Sloan et al reported that trauma patients with an SI ≥1.0, 1.4 and 1.8 at any time point were 2.3, 2.7 and 3.1 times, respectively, more likely to die within 28 days than were patients with SI values below these cut-offs (p<0.001). In the same study, and after 120 min of resuscitation, patients with an SI ≥1.0 were 3.9 times more likely to die within 28 days (40% vs 15%, p<0.001) 24. A recent retrospective study of 20 000 adult patients from the trauma registry demonstrated that an SI of ≥1.4 was associated with worst injury severity score, largest fluid requirements, greatest transfusion requirements and highest proportion of patients transfused.…”
Section: Discussionmentioning
confidence: 84%
“…Its predicting value for the outcome has been fully demonstrated in the patients with trauma [1][2][3][4]. Recently, some studies further showed that a new index, MSI, in the ED is a more valuable marker for predicting the mortality rate than SI alone in adult patients with trauma [14].…”
Section: Discussionmentioning
confidence: 97%
“…It has been demonstrated as a useful predictor for hospital mortality among adult patients with trauma [1][2][3]. Shock index is better not only than SBP, diastolic blood pressure (DBP), and HR alone but also than some risk stratification systems, for example, SI is more useful than the Triage Sort (TSO) for secondary triage in a mass-casualty situation [4].…”
Section: Introductionmentioning
confidence: 99%
“…Like DCLHb this Hb had a P 50 value close to that of normal red blood cells (RBCs). Some Phase I/II clinical trials in elective surgeries with Optro (5 g Hb/dL) were conducted but discontinued due to the hypertensive effects and other related adverse events [16]. …”
Section: Hboc Types and Indicationsmentioning
confidence: 99%